The Epistemology of MUI’s Fatwas on Covid-19: Bayani and Burhani Eclecticism - Mun'im, Zainul (Institut Agama Islam Negeri Curup, 2022)
This article aims to analyze the legal epistemology used in MUI’s fatwas related to Covid-19. This article focuses on the MUI’s fatwas on the Implementation of Friday and Congregational prayers to prevent the Transmission of the Covid-19 Pandemic and the Fatwa on Guidelines for managing the body (tajhiz al-jana'iz) of a Muslim infected with the Covid-19. This study is library research with qualitative methods. This article shows that MUI uses two epistemologies in its fatwas. The first is the epistemology of bayani, which is mainly derived from the authority of the Quran and Sunnah. This epistemology serves to establish the principle of law in the fatwa. The second is the epistemology of burhani, which is based on rational-empirical arguments. This epistemology serves to find out how dangerous the Covid-19 virus is. The two epistemological branches used by MUI above are an attempt to combine textual and rational-empirical arguments. Based on the eclecticism of these two epistemologies, the fatwa issued by MUI is more in line with the realities of today's life, especially regarding the reality of health during the pandemic of Covid-19.